Achieving Transparency: An Argument For Enactivism. (8th May 2015) - Ward, Dave
Abstract : The transparency of perceptual experience has been invoked in support of many views about perception. I argue that it supports a form of enactivism—the view that capacities for perceptual experience and for intentional agency are essentially interdependent. I clarify the perceptual phenomenon at issue, and argue that enactivists should expect to find a parallel instance of transparency in our agentive experience, and that the two forms of transparency are constitutively interdependent (Section 1). I then argue that i) we do indeed find such parallels: the way in which an action is directed towards its goal through our bodily movements parallels the way in which an experience is directed towards its object through our perceptual sensation (Section 2), and ii) reflecting on sensorimotor skills shows why the two instances of transparency are constitutively interdependent (Section 3). Section 4 gives reasons for generalizing beyond the cases considered so far by applying the enactive view to Kohler's landmark studies of perceptual adaptation. The final section clarifies the form of enactivism to which the previous sections point. The view that emerges is one whereby our perceptual and practical skills are interrelated aspects of a single capacity to have one's mind intentionally directed upon the world. The transparency of experience, on this view, is achieved in virtue of our capacities as agents as much as it is given in virtue of our capacities as perceivers.